The cost of ignorance: reputational mark-up in the market for Tuscan red wines. Issue 2 (11th November 2021) - Pedersen, Maja Uhre; Sharp, Paul
Abstract : Purpose: The purpose of this paper is to provide an empirical investigation of the idea that imperfectly informed consumers use simple signals to identify the characteristics of wine, for example, the geographical denomination. The reputation of a denomination will thus be an important guide for consumers when assessing individual wines. Design/methodology/approach: The price–quality relationship is studied in a fairly homogenous geographical area where a large number of wine types is present. This is done by using a simple ordinary least squares (OLS) analysis on a database of more than 2, 000 different red wines produced in a period of just four years in only one Italian region. Findings: The results show that some denominations have a lower average quality score and that price differentials between denominations are linked to differences in average quality, although consumers tend to exaggerate the quality gap between prestigious denominations and others. Research limitations/implications: A producer in a prestigious denomination benefits from a substantial mark-up relative to an equally good producer from another denomination. Furthermore, denomination neutral wines have a stronger price–quality relationship than denomination specific wines. Practical implications: Consumers should not be misled by what is on the bottle, but should rather consult wine guides to become better informed before purchasing. Social implications: The fact that quality and sensory characteristics often play a minor role in determining the price of a commodity is not immediately compatible with the postulate that consumers are well informed. Originality/value: Unlike previous work, this paper investigates a limited area (Tuscany) and only red wines, thus making it possible implicitly to control for many other factors which might otherwise confound the price–quality relationship.